2021
DOI: 10.21744/irjmis.v8n2.1100
|View full text |Cite
|
Sign up to set email alerts
|

formative assessment as systematic practice in higher basic education students

Abstract: In the educational field, evaluation is a widely used term but generally associated with qualification, measurement, or as a promotional item from year to year. So, it is essential to reflect on the use given to it, in educational contexts. The objective was to analyze the perspective of teachers and students to the formative evaluation and their contribution to the improvement of the teaching-learning process, of the tenth-year students of a Fiscal Educational Unit in the city of Manta. The quantitative metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In addition, organizations with a positive attitude toward equal opportunity programs frequently employ mentorship and networking to develop gender-specific strategies for overcoming prejudice. According to numerous studies, proper training and career development significantly impact women's career development (Cobeña et al, 2021;Sintani et al, 2021). Fritsch (2015), found that women managers in Europe perceive a lack of opportunities to network with senior management as a significant obstacle to their career advancement, supporting this study's findings.…”
Section: Equal Opportunitysupporting
confidence: 74%
“…In addition, organizations with a positive attitude toward equal opportunity programs frequently employ mentorship and networking to develop gender-specific strategies for overcoming prejudice. According to numerous studies, proper training and career development significantly impact women's career development (Cobeña et al, 2021;Sintani et al, 2021). Fritsch (2015), found that women managers in Europe perceive a lack of opportunities to network with senior management as a significant obstacle to their career advancement, supporting this study's findings.…”
Section: Equal Opportunitysupporting
confidence: 74%
“…Before that, the project method was called the "problem method" or "target act method". In 1911, the US Bureau of Education legalized the term "project"; it began to become more and more firmly established in American pedagogy (Cobeña et al, 2021;Lefebure, 2019). The universal use of the project method led to its new definition, which was given by the teacher, a philosopher and a colleague of J. Dewey, Professor W. Kilpatrick.…”
Section: The Origin Of the Project Methodsmentioning
confidence: 99%
“…According to the results observed, it can be seen that only 7% indicated that they always, while the great majority, that is to say 93%, maintained that they had never received any type of training. In this work it was also possible to determine that school dropout is determined by extracurricular variables, which are directly related to the socioeconomic situation and the family context of the students, including poverty and marginality, job search, teenage pregnancy, family dysfunction, alcohol and drug use, educational levels of parents, lack of follow-up and family support due to low expectations of the family regarding education, migration of parents, abuse in the use of technology such as TV, electronic equipment and games, as well as the Internet with its social networks and pornography (Farmer et al, 2003;South et al, 2007;Cobeña et al, 2021).…”
Section: Aspects To Be Considered In School Dropoutmentioning
confidence: 99%